2002
DOI: 10.1159/000059405
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Interleukin-8 Receptors CXCR1 and CXCR2 on Cord-Blood-Derived Cultured Human Mast Cells

Abstract: Background: An increase in mast cell number at sites of inflamed tissues has been observed. However, the expression of CXC chemokine receptors on human mast cells is poorly understood. Methods: Cultured human mast cells were raised from human umbilical cord blood cells in the presence of stem cell factor and interleukin-6 (IL-6). The expression of surface chemokine receptors on the mast cells was analyzed by flow cytometry and that of mRNA was examined by the method of reverse transcriptase-polymerase chain re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 23 publications
(42 reference statements)
4
16
0
Order By: Relevance
“…Chemokines are thought to contribute to the pathogenesis of allergic disease by regulating the migration of the cells that orchestrate the inflammation associated with these disorders, including mast cells, [29][30][31][32] and it has been proposed that mast cell migration at such sites may be regulated, in part, by RANTES and IL-8. 33, 34 We have confirmed that our HUCBMCs express receptors that can bind IL-8-that is, the chemokine receptors, CXCR1 and CXCR2 (data not shown). Moreover, Inamura et al 34 reported the dose-dependent migration of HUCBMCs in response to as little as 1 ng/mL IL-8.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Chemokines are thought to contribute to the pathogenesis of allergic disease by regulating the migration of the cells that orchestrate the inflammation associated with these disorders, including mast cells, [29][30][31][32] and it has been proposed that mast cell migration at such sites may be regulated, in part, by RANTES and IL-8. 33, 34 We have confirmed that our HUCBMCs express receptors that can bind IL-8-that is, the chemokine receptors, CXCR1 and CXCR2 (data not shown). Moreover, Inamura et al 34 reported the dose-dependent migration of HUCBMCs in response to as little as 1 ng/mL IL-8.…”
Section: Discussionsupporting
confidence: 68%
“…33, 34 We have confirmed that our HUCBMCs express receptors that can bind IL-8-that is, the chemokine receptors, CXCR1 and CXCR2 (data not shown). Moreover, Inamura et al 34 reported the dose-dependent migration of HUCBMCs in response to as little as 1 ng/mL IL-8.…”
Section: Discussionsupporting
confidence: 68%
“…In human macrophages and macrophage-derived foam cells, CCL15 is capable of inducing the production of MMP-9 (27), whose expression is regulated by STAT3 (28), whereas CXCL8 is apparently involved in the recruitment of human NK cells to sites of early viral infection by mast cells (61) and metastasis of colon cancer (62). The release of CXCL8 activates CXCR2, which is coexpressed with CCR1 in macrophages (39) and human mast cells (63,64), leading to STAT3 Tyr 705 phosphorylation (65). Hence, the production of CXCL8 mediated by CCR1/Ga 14/16 may create another loop of STAT3 activation, which synergizes with the effect on CXCL8 secretion.…”
Section: Discussionmentioning
confidence: 99%
“…CXCR2 is expressed on a broad range of leukocytes, including neutrophils, monocytes/macrophages, eosinophils, mast cells, basophils and lymphocytes [24][25][26][27][28]. The physiological function of CXCR2, however, has been most extensively studied in neutrophils.…”
Section: Leukocytesmentioning
confidence: 99%